LITERAL AND FREE TRANSLATION IN LITERARY TRANSLATION. - Abdirasulova Umida Abdirizvon qizi , (TADQIQOTLAR.UZ, 2023)
Abstract: Translation is converting the meaning and context of a text from one language to another. Literal translation is the rendering of a text from one language to another one word at a time, without considering the meaning of the text as a whole, while free translation is translating a text in such a way that it reproduces the general meaning of the original text. This article talks about literal translations and free translations are types of translations.